Palliative Care as a Form of Relief for the Dying: A South African Perspective - Welgemoed, Marc; Lerm, Henry (Obiter, 2020)
This article has a critical look at the current state of affairs in palliative care in South Africa. While euthanasia remains unlawful in South Africa, there is only one alternative – namely, palliative care – to mitigate pain and symptoms, make life tolerable, and ease the emotional stress of dying for patients and their families. Palliative care, unlike euthanasia, has always been regarded as a sound medical practice, ethically, morally and legally. The practice the world over includes family, friends and community. However, no system or legislation has been put in place in South Africa to serve as a guideline for end-of-life practices. The focus of this article is to try to establish guidelines through a multidisciplinary approach that includes the family and makes use of community resources to improve the quality of life of patients and families facing the problems associated with life-threatening illness, through the prevention and relief of suffering.